The AMPK agonist 5‐aminoimidazole‐4‐carboxamide ribonucleotide (AICAR), but not metformin, prevents inflammation‐associated cachectic muscle wasting. Issue 7 (29th May 2018) - Hall, Derek T; Griss, Takla; Ma, Jennifer F; Sanchez, Brenda Janice; Sadek, Jason; Tremblay, Anne Marie K; Mubaid, Souad; Omer, Amr; Ford, Rebecca J; Bedard, Nathalie; Pause, Arnim; Wing, Simon S; et al.
Abstract: Activation of AMPK has been associated with pro‐atrophic signaling in muscle. However, AMPK also has anti‐inflammatory effects, suggesting that in cachexia, a syndrome of inflammatory‐driven muscle wasting, AMPK activation could be beneficial. Here we show that the AMPK agonist AICAR suppresses IFNγ/TNFα‐induced atrophy, while the mitochondrial inhibitor metformin does not. IFNγ/TNFα impair mitochondrial oxidative respiration in myotubes and promote a metabolic shift to aerobic glycolysis, similarly to metformin. In contrast, AICAR partially restored metabolic function. The effects of AICAR were prevented by the AMPK inhibitor Compound C and were reproduced with A‐769662, a specific AMPK activator. AICAR and A‐769662 co‐treatment was found to be synergistic, suggesting that the anti‐cachectic effects of these drugs are mediated through AMPK activation. AICAR spared muscle mass in mouse models of cancer and LPS induced atrophy. Together, our findings suggest a dual function for AMPK during inflammation‐driven atrophy, wherein it can play a protective role when activated exogenously early in disease progression, but may contribute to anabolic suppression and atrophy when activated later through mitochondrial dysfunction and subsequent metabolic stress. Synopsis: Cachexia is a co‐morbidity characterized by the loss of skeletal muscle that arises in patients with pro‐inflammatory diseases, like cancer. Activators of AMPK were found to protect against inflammation‐induced muscle atrophy, demonstrating the potential of targeting AMPK for therapy in cachexia. The AMPK activator AICAR, but not metformin, protected C2C12 myotubes from IFNγ/TNFα‐driven atrophy. The differential effects of AICAR and metformin were associated with the ability to restore or inhibit mitochondrial function during inflammation, suggesting that the mechanism of AMPK activation affects the outcome of treatment. The anti‐cachectic properties of AICAR were impaired by treatment with the AMPK inhibitor Compound C and were synergistic with the AMPK activator A‐769662, suggesting that the effects of AICAR were mediated by AMPK activation. AICAR, but not metformin, was effective at preventing muscle mass loss in mice in both the C26 model of cancer cachexia and an endotoxin model of sepsis. Collectively, this study suggests that treatment with AMPK activators during the early stages of cachexia could be a novel avenue for the development of therapies. Abstract : Cachexia is a co‐morbidity characterized by the loss of skeletal muscle that arises in patients with pro‐inflammatory diseases, like cancer. Activators of AMPK were found to protect against inflammation‐induced muscle atrophy, demonstrating the potential of targeting AMPK for therapy in cachexia.